2012
DOI: 10.5539/jas.v4n10p175
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds and Antioxidant Activity from Saffron (Crocus sativus L.) Petal

Abstract: Saffron petal is the main by-product of saffron processing which is producing in large amounts annually. The purposes of this work were to determine total phenolics content in the methanolic extract of saffron petal using Folin-ciocalteu reagent and to measure their antioxidant activity in various in vitro models, such as β-carotene-linoleate and 1,1-diphenyl-2-picryl hydrazyl (DPPH). Saffron petal extract in different concentrations (0.5-5 mg ml -1 ) were compared with standard antioxidants of ascorbic acid, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 26 publications
2
14
0
1
Order By: Relevance
“…The technique and the solvent used can influence the extraction performance, but other factors can also affect the concentration of phytocompounds for saffron, such as provenance [47], conditions of growth [2,3], and storage [48]. Compared to the average value of TPC (1127.94 ± 32.34 mg GAE 100 g −1 DW), Lahmass et al [39] attained higher TPC from saffron dried tepals using maceration with both pure methanol (~9400 mg GAE 100 g −1 DW) and ethyl acetate (~4200 mg GAE 100 g −1 DW), while a lower TPC (~342 mg GAE 100 g −1 DW) was found by Amir et al [49] using UAE with pure methanol. The values of TPC were lower compared to those found in saffron spice (1819.5 mg GAE 100 g −1 DW) by Caser et al [2], but higher than those obtained from some traditional Chinese medicinal plants [50], such as Lycopus lucidus (~930 mg GAE 100 g −1 DW for methanolic extract of aerial parts), Smilax glabra (~740 mg GAE 100 g −1 DW for methanolic extract of root), Plantago asiatica (~850 mg GAE 100 g −1 DW for aqueous extract of seeds), Lobelia chinensis (~600 mg GAE 100 g −1 DW for aqueous extract of whole plant), Lithospermum erythrorhizon (~920 mg GAE 100 g −1 DW for root extract), Dianthus superbus (~690 mg GAE 100 g −1 DW for aqueous extract of aerial parts), Curcuma longa (~800 mg GAE 100 g −1 DW for rhizome methanolic extract), and Zingiber officinale (~740 mg GAE 100 g −1 DW for rhizome methanolic extract), as well as from some common vegetables and fruits [50], such as spinach (Spinacia oleracea,~900 mg GAE 100 g −1 DW for methanolic extract) and lettuce (Lactuca sativa,~780 mg GAE 100 g −1 DW for methanolic extract).…”
Section: Discussionmentioning
confidence: 84%
“…The technique and the solvent used can influence the extraction performance, but other factors can also affect the concentration of phytocompounds for saffron, such as provenance [47], conditions of growth [2,3], and storage [48]. Compared to the average value of TPC (1127.94 ± 32.34 mg GAE 100 g −1 DW), Lahmass et al [39] attained higher TPC from saffron dried tepals using maceration with both pure methanol (~9400 mg GAE 100 g −1 DW) and ethyl acetate (~4200 mg GAE 100 g −1 DW), while a lower TPC (~342 mg GAE 100 g −1 DW) was found by Amir et al [49] using UAE with pure methanol. The values of TPC were lower compared to those found in saffron spice (1819.5 mg GAE 100 g −1 DW) by Caser et al [2], but higher than those obtained from some traditional Chinese medicinal plants [50], such as Lycopus lucidus (~930 mg GAE 100 g −1 DW for methanolic extract of aerial parts), Smilax glabra (~740 mg GAE 100 g −1 DW for methanolic extract of root), Plantago asiatica (~850 mg GAE 100 g −1 DW for aqueous extract of seeds), Lobelia chinensis (~600 mg GAE 100 g −1 DW for aqueous extract of whole plant), Lithospermum erythrorhizon (~920 mg GAE 100 g −1 DW for root extract), Dianthus superbus (~690 mg GAE 100 g −1 DW for aqueous extract of aerial parts), Curcuma longa (~800 mg GAE 100 g −1 DW for rhizome methanolic extract), and Zingiber officinale (~740 mg GAE 100 g −1 DW for rhizome methanolic extract), as well as from some common vegetables and fruits [50], such as spinach (Spinacia oleracea,~900 mg GAE 100 g −1 DW for methanolic extract) and lettuce (Lactuca sativa,~780 mg GAE 100 g −1 DW for methanolic extract).…”
Section: Discussionmentioning
confidence: 84%
“…The total phenolic and flavonoid contents of SPE in this study were 4.29 (mg of GAE/g of powder extract) and 2.75 (mg QE/g of powder extract), respectively. Goli et al [8] and Termentzi and Kokkalou [28], respectively, reported total phenolic contents of 3.35 and 1.38 mg/g for Iranian saffron petal. Significantly greater amounts of total phenolic components (65.34 mg of GAE/g of powder extract) and flavonoids (60.64 mg CE/g of dry plant material) have been reported by Jadouali et al [29].…”
Section: Discussionmentioning
confidence: 99%
“…Saffron petal, as an important by-product of saffron, is produced in large amounts annually (more than 10,000 tons/yr) and usually discarded as a waste product [7]. The reported antioxidant properties of saffron petal [8,9] are more likely attributed to its phenolic compounds, such as crocin and kaempfrol [10]. However, there are limited studies on the effects of saffron petal, and/or its bio-active compounds, as an antioxidant source for ruminant animals.…”
Section: Introductionmentioning
confidence: 99%
“…Već na ovom nivou moguće je uočiti relativan doprinos faktora vrste sadnica na jesenjm plotu sadnje, Budući da su fenolna jedinjenja ispoljavaju širok spektar aktivnosti (Janković, 2005;Zheng i Wang, 2001;Hossein Goli et al 2012;Saravanakumar et al 2009;Wojdylo et al 2007) i zbog sposobnosti flavonoida da redukuju slobodne radikale kao što su superoksid, peroksil, alkosil i hidroksil radikali (Pietta, 2000), očekivalo se da razlika između antioksidativne aktivnosti ekstrakta koji je imao najveću sumu kvantifikovanih jedinjenja (F max) i ekstrakta sa najmanjim sadržajem (F min) biti izražena. Međutim aktivnosti ova dva ekstrakta su bile gotovo ujednačene.…”
Section: Međusobni Odnosi Testiranih Karakteristikaunclassified